What Do We Know About 21st Century Youth? American Teens Through the Eyes of a Psychologist - Anita Poplavskaya (Journal of Economic Sociology, 2020)
A book written by American psychologist Jean M. Twenge iGen. Why Today's Super-Connected Kids Are Growing Up Less Rebellious, More Tolerant, Less Happy—and Completely Unprepared for Adulthood—and What That Means for the Rest of Us describes the change in values, identity and behavior of adolescents born during the period from 1995 to 2012, the Internet Generation known as iGens. The book represents a good example of thorough data analysis, using the results of sociological surveys that originated in the 1960`s and covering opinions of more than 11 million Americans. Guided by such extensive empirical material, the author infers that adolescents have begun to grow up more slowly, plunge into the virtual world at the expense of reality, presume upon new media, communicate less, and show less interest in news. All that led to a degradation of knowledge and skills, a lack of sophistication, the growth of mental disorders, a lack of self-confidence, angst, and the spread of perverse attitudes towards education, work, family and money. The main reasons for such fundamental changes lie in the safer environment of iGens’ childhoods as well as their greater involvement in digital technologies and information. Accustomed to being supervised externally, iGens internally dive into virtual reality, lose interest in extracting knowledge themselves (reducing their ability to overcome obstacles or desire to take risks), and receive much less real experience. iGens are a few times less likely to meet friends, go on dates, get professional experience, drive a car, drink alcohol, read books, or keep up on the news than representatives of generations X and Y. At the same time, iGens spend twice as much time on the Internet than millennials. Uncontrollably and indiscriminately absorbing primitive and chaotic information, modern adolescents lose their integrity. This is evidenced by the growth of anxiety, mental disorders, and suicides. The example of American teenagers shows that people might lose the very abilities for which the technologies have been created (e. g. interpersonal communication, critical thinking, information awareness, creativity, personal growth, safety, etc.).